Acclimation to drought stress improves root physiology and cell mitotic index, leave pigments and water status in Oryza sativa L. - Rosely, N.F.S.; Saimi, N.N.; Midin, M.R.; Karim, M.F. (International Journal of Biology and Chemistry, 2024)
Drought is a prominent abiotic stressor that critically impairs rice productivity by disrupting fundamental physiological processes and diminishing yield potential. This study investigates the effects of continuous and alternating drought stress on cell mitotic index and physiological responses in selected traditional and domestically grown rice varieties. Drought stress was imposed for approximately 9 days, a condition visibly marked by the rolling of leaves. In the alternating drought treatment, plants were exposed to identical drought conditions but were rehydrated to normal water levels on the 10th day, with this cycle of drought and rehydration repeated twice. Continuous drought stress led to a significant reduction in root cell mitotic activity, with a decrease ranging from 23.6% to 67% compared to control conditions. Additionally, drought stress adversely impacted leaf physiology, evidenced by reductions in total chlorophyll content, Fv/Fm ratios, and relative leaf water status. In contrast, the severity of these physiological disruptions was less pronounced in plants subjected to alternating drought stress. In addition, while acclimated plants exhibited elevated levels of root electrolyte leakage (REL) and malondialdehyde (MDA) compared to controls, these levels were substantially lower than those observed under continuous drought stress. These findings suggest that while drought negatively affects most physiological parameters, its impact can be mitigated through intermittent watering and the use of drought-tolerant rice varieties.